Incidence of deep vein thrombosis in patients with pelvic and acetabulum fractures requiring operative intervention in Hospital Universiti Sains Malaysia : is preoperative screening with doppler ultrasound necessary? - Deyoi, Yolanda Boniface (2021)
Introduction Pelvic and acetabulum fractures commonly occur due to high impact injury putting patients at higher risk of developing thromboembolic diseases such as deep vein thrombosis and pulmonary embolism. This study was performed to determine the incidence of lower extremity deep vein thrombosis in patients with pelvic and acetabulum fractures to determine the importance of preoperative screening with Doppler ultrasound prior to surgical intervention. Materials and methods This was a retrospective study involving 78 patients admitted to Hospital Universiti Sains Malaysia with pelvic and acetabulum fractures requiring surgical intervention from January 2015 till December 2019. All patients planned for surgical intervention were screened preoperatively with Doppler Ultrasound to detect for lower limb DVT. These were compared with incidence of lower limb DVT post operatively. Descriptive statistical analysis was performed using IBM SPSS Statistics Version 24. Results There were 78 patients included in this study consisting of 30.8% females and 69.2% male patients. Preoperative screening with Doppler ultrasound showed 3 (3.8%) patients were diagnosed with lower limb DVT whereas 1 (1.3%) was symptomatic and diagnosed with PE. Postoperatively, 1 patient developed DVT and 1 patient developed PE. Both of these patients were negative for DVT preoperatively. Conclusion The incidence of VTE in patients with pelvic and acetabulum fractures in our centre based on preoperative screening is low but is significantly important to prevent further morbidity and mortality. However, negative preoperative screening cannot safely rule out patients from developing VTE postoperatively. Despite initiation of thromboprophylaxis in trauma patients, we cannot prevent the incidence of venous thromboembolic diseases. We recommend preoperative screening with Doppler ultrasound prior to operative intervention to detect DVT especially in asymptomatic patients with pelvic and acetabulum fractures to be included in our Malaysian Clinical Practice Guidelines for management of DVT.